The effect of Er3+ concentration on the kinetics of multiband upconversion in NaYF4:Yb/Er microcrystals - Huang, Hanchang; Zhong, Yanyi; Li, Mingchen; Cui, Wenda; Yu, Tongcheng; Zhao, Guomin; Xing, Zhongyang; Guo, Chuan; Han, Kai (Frontiers in Chemistry, 2023)
In Yb-Er co-doped upconversion (UC) nanomaterials, upconversion luminescence (UCL) can be modulated to generate multiband UCL by changing the concentration of activator Er3+. However, the kinetics of these multiband emissions affected by the Er3+ concentrations remain unclear. In this work, we studied the single β-NaYF4:Yb3+/Er3+ microcrystal (MC) doped with different Er3+ concentrations by nanosecond time-resolved spectroscopy. Interestingly, different Er3+ doping concentrations exhibit different UCL emission bands and UCL response rates. At low Er3+ doping concentrations (1 mol%), multiband emission in β-NaYF4:Yb3+/Er3+ (20/1 mol%) MCs could not be observed and the response rate of UCL was slow (5-10 μs) in β-NaYF4:Yb3+/Er3+. Increasing the Er3+ doping concentration to 10 mol% can shorten the distance between Yb3+ and Er3+, which facilitates the energy transfer between Yb3+ and Er3+. β-NaYF4:Yb3+/Er3+ (20/10 mol%) can achieve obvious multiband UCL and quick response rate(0.3 μs). However, further increase of Er doping concentration (80 mol%) makes MCs limited by the CR process and cannot achieve the four-photon UC process (4F5/2 → 2K13/2 and 2H9/2 → 2D5/2). The result shows that varying the Er3+ doping concentration provides a way to control the energy flow between energy levels of Er3+ ions, which can modulate the response time and UCL emitting on Yb/Er doped materials. This can direct the prospective development of fast-respond optoelectronic devices, photocatalysis, and UC displays in the future.